ANALYSIS OF THE GODLY CONSTITUTION TOWARDS TRADITIONAL BELIEFS IN INDONESIA - Failaq, Muhammad RM Fayasy; Adnan, Muhammad; Al-Farouq, Muhammad Umar (LPPM Universitas Muria Kudus, 2025)
In the beginning, traditional beliefs in Indonesia were always rejected. Even RI Presidential Decree No. 1/PNPS 1965 provides criminal sanctions against individuals who adhere to traditional beliefs that defame religion. Even though Constitutional Court Decision No. 97/PUU/VIX/2016 was later acknowledged, its conception remains questionable. Moreover, with the characteristics of the 1945 Constitution of the Republic of Indonesia which is a constitutional constitution based on God; there is a gray area regarding the relevance of traditional beliefs to the identity of such a constitution. The method used is socio-legal with a legal approach in the form of a statutory approach, a conceptual approach, and a religious studies approach. Data was obtained from the literature and analyzed qualitatively. This research concludes that the concept of constitutional identity is part of the constitutional identity that is accommodated in Indonesia. Beliefs that have the dimension of trust in an entity that has power can be analyzed using this concept to examine the suitability and explore the philosophical basis in the Indonesian legal system. Finally, the acceptance of traditional beliefs in Indonesia is due to two philosophical legitimations, namely a godly constitution (slightly) due to its characteristics in traditional beliefs, and a cultural constitution that respects the existence of traditional beliefs as cultural identities and traditional rights.